A CORPUS BASED STYLISTIC ANALYSIS OF SELECTED CHILDREN’S POEMS (Contemporary Journal of Social Science Review, 2025)
Children’s literature holds a special place in literary and educational discourse. This research seeks to contribute significantly to both corpus stylistics and children’s literature studies. It aims to uncover and analyze the thematic elements and linguistic expressions in Young World Magazine and V shine magazine with the goal of shedding light on the role of children’s selected poems in shaping young minds. The study uses corpus technique merging with a descriptive qualitative methodology to identify themes and expressions. A thematic analysis was performed to determine recreating themes in the selected children's poetry. Data for this study is collected from two popular English magazines, Young World and Vshine, known for their diverse selection of children's poetry. The process of data collection includes the acquisition of data in soft form. These magazines provide a rich source of contemporary children's literature, spanning various themes, styles, and cultural backgrounds. After collection, data was added in PakLocCorpus data sets for further analysis. Data consists of 232 files and a 16850 number of words. It was developed under the category of poems. PakLocCorpus consists of more than 10 million words of Pakistani English.